Pengukuran Kualitas Jaringan Internet Dengan Sinyal 3G Lte Pada STMIK Budi Darma Medan dengan Metode Quality Of Service (QoS) - Sinaga, Sony Bahagia; Hasan, Yasir (MEANS (Media Informasi Analisa dan Sistem), 2018)
In today's age the internet needs are very important for communicating or looking for information. The longer the development of the internet network is increasingly widespread such as 1G, 2G, 3G and 4G technologies. Long Term Evolution (LTE) is a long-term radio evolution access network issued by the 3rd (Generation Partnership Project). To improve internet network services at STMIK Budidarma, testing and measurement are carried out using the Quality Of Service (QoS) method to determine the quality and power of data transfer. The Quality Of Service (QoS) method found on a TCP / IP network is one that focuses on allocating bandwidth within the internet network that flows fairly and as needed. The QoS method that relies on testing the process of delay time, latency time, packet request time and creating a network topology to reduce the risk that arises.